Effect of Phyllanthus emblica Linn. on tensile strength of virgin and bleached hairs - Pratya Tiampasook (2020)
© 2020 by the authors. In Ayurveda medicine, Phyllanthus emblica Linn. (emblica) has been used as a hair nourisher for more than a decade by soaking it overnight, but no study has proved the effect of emblica on hair. This research aims to determine the effect of emblica solution on the tensile strength of three types of hair: virgin hair (VH), bleached hair (BH), and twice bleached hair (TH). The investigated active substances were deionized water (DI water) as a control, 3% emblica extract solution (3% EXS), 6% emblica extract solution (6% EXS), and 9% emblica extract solution (9% EXS). Black Virgin Asian hair was measured and analyzed before bleaching with a 12% bleaching agent once (BH) and twice (TH). Three treatments and the control were applied to each type of hair under a controlled condition. The tensile characteristics and surface morphology of all treated hairs were measured and analyzed by texture analysis (TA.XT Plus Texture Analyzer, Stable Micro Systems), Aramo (Aramo-SG Skin & Hair analysis system), and scanning electron microscopy (SEM model JSM-5410LV JEOL). The results of the nanoindentation test proved that the tensile strength and extensibility of all three types of hair increased in all concentrations (DI water, 3% EXS, 6% EXS, and 9% EXS). High magnification SEM images were taken from the cuticle surfaces and cross-sections. Emblica extracted solution (EXS) formed a coating around the hair, especially cuticle damaged by bleaching (BH and TH). The breaking pattern from the cross-section images showed that emblica extract solution reinforced all hair types. In conclusion, the emblica extract solution has a significant positive effect on the tensile strength and extensibility of VH, BH, and TH. The result has proved the ancient intelligence that the emblica nourishes the hair. In addition, our results show additional benefit by strengthening virgin hair and bleached hair.